Uniaxial Cyclic Stretching Promotes Chromatin Accessibility of Gene Loci Associated With Mesenchymal Stem Cells Morphogenesis and Osteogenesis - Zhang, Duo; Zhang, Ran; Song, Xiaoyuan; Yan, Karen Chang; Liang, Haiyi (Frontiers in Cell and Developmental Biology, 2021)
It has been previously demonstrated that uniaxial cyclic stretching (UCS) induces differentiation of mesenchymal stem cells (MSCs) into osteoblasts in vitro. It is also known that interactions between cells and external forces occur at various aspects including cell-matrix, cytoskeleton, nucleus membrane, and chromatin. However, changes in chromatin landscape during this process are still not clear. The present study was aimed to determine changes of chromatin accessibility under cyclic stretch. The influence of cyclic stretching on the morphology, proliferation, and differentiation of hMSCs was characterized. Changes of open chromatin sites were determined by assay for transposase accessible chromatin with high throughput sequencing (ATAC-seq). Our results showed that UCS induced cell reorientation and actin stress fibers realignment, and in turn caused nuclear reorientation and deformation. Compared with unstrained group, the expression of osteogenic and chondrogenic marker genes were the highest in group of 1Hz + 8% strain; this condition also led to lower cell proliferation rate. Furthermore, there were 2022 gene loci with up-regulated chromatin accessibility in 1Hz + 8% groups based on the analysis of chromatin accessibility. These genes are associated with regulation of cell morphogenesis, cell-substrate adhesion, and ossification. Signaling pathways involved in osteogenic differentiation were found in up-regulated GO biological processes. These findings demonstrated that UCS increased the openness of gene loci associated with regulation of cell morphogenesis and osteogenesis as well as the corresponding transcription activities. Moreover, the findings also connect the changes in chromatin accessibility with cell reorientation, nuclear reorientation and deformation. Our study may provide reference for directed differentiation of stem cells induced by mechanical microenvironments.